2019
DOI: 10.3390/nu12010035
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet Slows Down the Progression of Aging and Helps to Prevent the Onset of Frailty: A Narrative Review

Abstract: The aging population is rapidly increasing all over the world. This results in significant implications for the planning and provision of health and social care. Aging is physiologically characterized by a decrease in lean mass, bone mineral density and, to a lesser extent, fat mass. The onset of sarcopenia leads to weakness and a further decrease in physical activity. An insufficient protein intake, which we often observe in patients of advanced age, certainly accelerates the progression of sarcopenia. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 173 publications
(171 reference statements)
1
58
0
4
Order By: Relevance
“…Studies have suggested that diet and nutrition may play a role in the development of AD [ 18 ]. The Mediterranean diet (MeDi) is associated with a lower incidence of chronic diseases and shows protective effects against cognitive decline in aging individuals [ 19 , 20 , 21 , 22 ]. Conversely, the overconsumption of high-sugar and high-fat diets coupled with sedentary lifestyle predisposes individuals to metabolic diseases and neurocognitive defects during the aging process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that diet and nutrition may play a role in the development of AD [ 18 ]. The Mediterranean diet (MeDi) is associated with a lower incidence of chronic diseases and shows protective effects against cognitive decline in aging individuals [ 19 , 20 , 21 , 22 ]. Conversely, the overconsumption of high-sugar and high-fat diets coupled with sedentary lifestyle predisposes individuals to metabolic diseases and neurocognitive defects during the aging process.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [ 27 , 28 , 29 , 30 , 31 ] have shown that increased adherence to the MedDiet (AMedDiet) reduces the risk of chronic diseases such as cardiovascular disease, BP, type II diabetes mellitus, cancer, mortality risk, etc., and increases life expectancy and quality of life. Due to the importance of a balanced and healthy diet, along with an adequate level of physical activity, which increases CRF and energy expenditure to prevent overweightness and obesity and to improve health-related quality of life in aging, studies that address this issue and propose solutions or intervention strategies are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The diet will follow the recommendations of a nutritionist in accordance with Davis et al [ 49 ] and the main recommendations are ≥5 servings of vegetables/day; ≥3 servings of fruit/day; ≥3 serves of fish or seafood/week; ≥3 servings of legumes/week; ≥3 servings of nuts/week; ≥5 servings of bread or cereals/day; preferentially consume white meat, instead of red meat; 2 to 4 servings of poultry/week and ≤1 serving of red meat/week; 2 to 4 servings of eggs/week; and using olive oil as the main oil for cooking and dressing.…”
Section: Methodsmentioning
confidence: 99%
“…[ 48 ] The MeDi is predominantly plant-based, with a high intake of vegetables, fruits, nuts, and legumes, moderately high intake of fish, low intake of red meat, and includes extra virgin olive oil. [ 49 ]…”
Section: Introductionmentioning
confidence: 99%